Incomplete Integration and Contagion of Debt Distress in Economic Unions - Karayalcin, Cem; Onder, Harun (World Bank, Washington, DC, 2014)
This paper compares different fiscal integration schemes on the basis of their ability to finance public investments and resilience to debt distress and contagion. Complete integration schemes, where a central authority chooses the level of public investments with productivity-enhancing externalities across different jurisdictions, are shown to be superior to incomplete integration schemes, where member governments choose public investments unilaterally. As a result, equilibrium income is greater for citizens of member states under a complete integration scheme. Moreover, complete integration schemes are shown to be more resilient to idiosyncratic shocks and more effective in limiting contagion of debt distress. This is mainly because the central authority can credibly borrow more without risking default than member states taken together can and it can "transfer resilience" across them if needed. These findings inform discussions on structural aspects of secular stagnation in Europe by emphasizing a potential challenge in the institutional design of fiscal responsibilities.